STRUKTUR, KATEGORI, DAN FUNGSI SOSIAL UNGKAPAN KEPERCAYAAN RAKYAT BAGI CALON ANAK DARO DI KENAGARIAN KOTO BARU KECAMATAN BAYANG KABUPATEN PESISIR SELATAN - Fadhla Hayati; Agustina Agustina; Nurizzati Nurizzati (Jurnal Bahasa dan Sastra, 2013)
This study aims to describe the structure, categories and social functions contained in the expression of the people’s confidence in the potential of Anak Daroin Kenagarian Koto Baru sub districk Bayang Regency Pesisir Selatan. This research is descriptive qualitative research method. Background This study was Kenagarian Koto Baru sub districk Bayang Regency Pesisir Selatan, while the study entry Phrase for aspiring young people’s confidence in Kenagarian Koto Baru Subdistrick Bayang Regency Pesisir Selatan in terms of structure, categories, and social function. Data acquisition from informants using recording techniques. The technique used to analyze the data as follows. (1) transcripts recordings into written language, (2) translating data into Indonesian, (3) analyzed the expression of the people’s trust structure for the prospective Anak Daro, (4) analyzing the expression of the people’s trust categories for candidates Anak Daro, (5) analyzing the expression of the people’s social functions for prospective Anak Daro, (6) Formulating research result in the from of reports.